Rancang Bangun Sistem Informasi Tracer Study Pada Teknik Informatika Universitas Nusa Putra - Nugraha, Nugraha; Anggun Fergina; Alamsyah, Zaenal; Parwati, Lusiana Sani; Iskandar, Alyanissa Putri (Computer Science and Information Technology, 2024)
This research aims to implement the Tracer Study information system in the Department of Information Engineering, Nusa Putra University, with a focus on needs analysis, system design, application development, and testing. This system is designed to manage alumni data, monitor career development, and collect relevant information for study program evaluation. The successful implementation of the system is expected to increase the efficiency and effectiveness of Tracer Study, make a positive contribution to curriculum development, and improve the quality of education at universities.